Environmental Education: Is It a Crucial Factor in Improving Pro-Environmental Behavior among Students? - Fitri, Dyah Ekawati Noor; Julianto (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2024)
By instructing students on pro-environmental behavior, early environmental education and training can start to establish pro-environmental behavior among student. To proof the value of environmental education in educating students about current environmental issues and their effects on public health and safety, as well as motivating them to adopt pro-environmental behaviors, a literature review is required. The review was based on nine studies from reputable international publications that were published in English between 2019 and 2023 and were selected based on title, population, objectives, and outcomes criteria. The articles were found in the ScienceDirect database. The review focuses mostly on establishing the effectiveness of environmental education in influencing pro-environmental behavior. The review also examines the ways in which students' perceptions of environmental education and their pro-environmental conduct are influenced by the interaction of internal and external influences. The study's findings demonstrate the significance of environmental education in influencing students' pro-environmental behavior. By providing students with reliable, accurate, and valid information, environmental education raises their awareness of environmental issues and promotes the development of pro-environmental behavior. Additional research on best practice design to rise pro-environmental behavior through environmental education can be developed from this study. More research is required on the topic of integrating more both internal and external factors of pro-environmental behavior in the environmental education curriculum.